Impact of American Joint Committee on Cancer 8th edition classification on staging and survival of patients with melanoma - Kanaki, Theodora; Stang, Andreas; Gutzmer, Ralf; Zimmer, Lisa; Chorti, Eleftheria; Sucker, Antje; Ugurel, Selma; Hadaschik, Eva; Gräger, Nikolai S.; Satzger, Imke; Schadendorf, Dirk; Livingstone, Elisabeth (European journal of cancer (1990), 2019)
The American Joint Committee on Cancer (AJCC) 8th staging system introduced several revisions. To assess the impact of the 8th edition American Joint Committee on Cancer (AJCC8) staging system on subgrouping and survival, patients with melanoma from two tertiary skin cancer centres were classified according to both the 7th edition American Joint Committee on Cancer (AJCC7) and AJCC8. A total of 1948 patients aged ≥18 years with cutaneous melanoma stage II-IV were included. The impact of sex and age on reclassification was assessed by log binomial models. The inverse probability of censoring weighting method was used to compute ROC curves from time-to-event data to assess the discriminatory ability of AJCC7 and AJCC8. Melanoma-specific survival (MSS) and overall survival (OS) were calculated, and age- and sex-adjusted MSS hazard ratios were estimated using Cox proportional hazards models. Of all, 23.5% of patients were assigned a different subgroup when classified according to AJCC8. Owing to upshifting to stage IIIC (AJCC7 24.8% vs. AJCC8 50.8%), patient numbers of stages IIIA and IIIB decreased from 28.7% to 16.2% and 46.5% to 28.3%. The prediction accuracy for AJCC7 and AJCC8 was comparable (integrated time-dependent area under the curve [AUC] of 0.75 and 0.74, respectively). Five-year MSS of IIB and IIC AJCC8 was poor and lower than that of IIIA AJCC8 (80%, 67% and 89%, respectively). Compared to results of the International Melanoma Database and Discovery Platform, 5-year MSS was 10–15% points lower for stages IIC, IIIB and IIIC. Upshifting affects primarily stage III subgroups, while effects in stage II are minor. Stage IIB/C (AJCC8) patients have 67–80% MSS and should be considered for adjuvant treatment, while in stage IIIA, the indication of adjuvant treatment is questionable. •Melanoma classification according to the 8th edition American Joint Committee on Cancer (AJCC8) does not improve discriminatory ability compared with the 7th edition American Joint Committee on Cancer (AJCC7).•Five-year melanoma-specific survival (MSS) of stages IIB/IIC is lower than that of IIIA.•MSS is worse in all substages than results of the International Melanoma Database and Discovery Platform cohort.